Sistema web para la gestión de la superación profesional en la Escuela Nacional de Salud Pública. 2019. - Brunet Salas, Iskania; Álvarez Lauzarique, María Esther; Paredes Esponda, Esther María (Revista Cubana de Informática Médica)
The National School of Public Health has contributed substantially to the training of human resources in the academic and professional areas of the Cuban health system, due to the development of an extensive program of academic postgraduate training and professional upgrading. The latter is characterized by the expansion of courses, trainings, diplomas, workshops, conferences and others, generating numerous professional development activities in the institution, all of them with insufficiencies in their management and devoid of computer technologies to provide improvements in their performance. For these reasons, a technological development research was carried out in 2019 with the aim of designing a web system for the management of professional development activities at the National School of Public Health. The AUP-UCI software development methodology was used, the Vue.js working environment written in JavaScript programming language and MongoDB as the database manager, and the Case Visual Paradigm tool of Unified Modeling Language. Some functionalities of the system were implemented, which are ready for the deployment phase. The proposed system satisfies the information needs for the improvement of professional upgrading in the institution, favors decision-making by managers, professors, and users linked to the process, shows great feasibility of its application and extension to other postgraduate educational institutions in health and other sectors.